Two new species of Phylloporia (Hymenochaetaceae, Basidiomycota) from the karst region in southern China - Shao, Yuanyuan; Zheng, Haifu; Huang, Haisi; Wei, Qiulu; Huang, Fuchang; Liu, Bin (Phytotaxa, 2025)
Two interesting taxa of Phylloporia from the karst region in southern China are described and illustrated as new species based on morphological characters and molecular data. Morphologically, the new species Phylloporia cryptolepidis is distinguished by its yellowish white to pale yellow pilei with light brown spots on the pore surface, and broadly ellipsoid to ellipsoid basidiospores measuring (3.6–4.6 × 2.5–3.5 μm); P. oropheae is characterized by thick solitary woody hard basidiomata with an acute margin, consistently woody-hard pilei with a brown base and pale-yellow margin, larger slightly refractive pores (3–4 per mm), and ellipsoid to oblong-ellipsoid basidiospores measuring 4.2–5.3 × 2.6–3.6 μm. Phylogenetically, the analysis based on ITS and nLSU datasets confirm that these species form two distinct clades within Phylloporia, supporting their recognition as new taxa. The integration of morphological and molecular evidence establishes Phylloporia cryptolepidis and P. oropheae as novel species with the genus Phylloporia.